Step 1) We can solve both equations for #2x# which is a common term:
Equation 1)
#2x + 3y = -7#
#2x + 3y - color(red)(3y) = -7 - color(red)(3y)#
#2x + 0 = -7 - 3y#
#2x = -7 - 3y#
Equation 2)
#2x - 7y = 7#
#2x - 7y + color(red)(7y) = 7 + color(red)(7y)#
#2x - 0 = 7 + 7y#
#2x = 7 + 7y#
Step 2) Equate the right sides of each equation and solve for #y#:
#-7 - 3y = 7 + 7y#
#-color(blue)(7) - 7 - 3y + color(red)(3y) = -color(blue)(7) + 7 + 7y + color(red)(3y)#
#-14 - 0 = 0 + (7 + color(red)(3))y#
#-14 = 10y#
#-14/color(red)(10) = (10y)/color(red)(10)#
#-7/5 = (color(red)(cancel(color(black)(10)))y)/cancel(color(red)(10))#
#-7/5 = y#
#y = -7/5#
Step 3) Substitute #-7/5# for #y# in the solution to either equation in Step 1 and calculate #x#. I will choose the second equation:
#2x = 7 + 7y# becomes:
#2x = 7 + (7 * -7/5)#
#2x = 7 + (-49/5)#
#2x = (7 xx 5/5) - 49/5#
#2x = 35/5 - 49/5#
#2x = -14/5#
#color(red)(1/2) xx 2x = color(red)(1/2) xx -14/5#
#1x = -14/10#
#x = -7/5#
The solution is: #x = -7/5# and #y = -7/5# or #(-7/5, -7/5)#